2009
DOI: 10.1002/cbm.745
|View full text |Cite
|
Sign up to set email alerts
|

The EssenCES measure of social climate: A preliminary validation and normative data in UK high secure hospital settings

Abstract: Although preliminary, these data suggest that the English version of EssenCES may be a valid tool for assessing the social climate of high secure hospital settings in the UK, but a larger research study is required, covering a wider range of psychiatric disorders, types of service and levels of security.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
89
12
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(127 citation statements)
references
References 17 publications
22
89
12
3
Order By: Relevance
“…The fact that the psychometric properties of the English EssenCES remained stable across such a diverse range of settings and that they are consistent with those reported in previous research (Howells et al, 2009;Schalast & Groenewald, 2009;Schalast et al, 2008) is strong evidence to support the validity of scores obtained using the English EssenCES.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The fact that the psychometric properties of the English EssenCES remained stable across such a diverse range of settings and that they are consistent with those reported in previous research (Howells et al, 2009;Schalast & Groenewald, 2009;Schalast et al, 2008) is strong evidence to support the validity of scores obtained using the English EssenCES.…”
Section: Discussionsupporting
confidence: 82%
“…Finally, the residents within more secure hospital settings were rated as less cohesive and supportive of each other than residents from conditions of lesser security, and the residents within more secure prison settings rated their unit as less safe than those from less secure prisons. These findings make sense theoretically and fit with the general pattern of findings observed in previous research using the EssenCES Howells et al, 2009;Long et al, 2010;Schalast et al, 2008) and with research using the WAS/CIES (Friis & Helldin, 1994;Langdon, Cosgrave, & Tranah, 2004;Langdon, Swift, & Budd, 2006;Moos & Schaefer, 1987).…”
Section: Validation Of the English Essences 16supporting
confidence: 87%
See 2 more Smart Citations
“…However, creating an optimal climate within a high security forensic setting can be very challenging due to the complex patient population, involuntary admission within a closed setting and the balance between security needs and treatment goals (Burrows, 1991;Campling, Davies, & Farquharson, 2004;Howells, Krishnan, & Daffern, 2007). Moreover, patients and staff members working within forensic psychiatric settings seem to evaluate ward climate differently (Caplan, 1993;Day, Casey, Vess, & Huisy, 2011;Dickens, Suesse, Snyman, & Picchioni, 2014;Howells et al, 2009;Livingston et al, 2012;Long et al, 2011;Moos, 1975;Rossberg & Friis, 2004;Schalast, Redies, Collins, Stacey, & Howell, 2008;Morrison, Burnard, & Phillips, 1997). For instance, Howells et al (2009) found that patients in a high secure hospital service in the United Kingdom (UK) evaluated cohesion among patients more favorably than staff members.…”
Section: Introductionmentioning
confidence: 99%